Fluorescence sensor using porous host molecules deposited on filter paper with vapochromic and mechanochromic properties. (12th January 2023) - Umezane, Sota; Fukutomi, Satoshi; Ono, Toshikazu; Hisaeda, Yoshio; Nishimura, Tomoki; Kawasaki, Riku; Ikeda, Atsushi
Abstract : Naphthalenediimide derivative-absorbed papers had fluorescence intensity and maximum depending on the type of guest aromatic molecules after exposure to vapors of small 10 guest molecules. Furthermore, the papers showed a mechanochromic property. Abstract : Naphthalenediimide derivative-absorbed papers, which were prepared by dropping chloroform solution, showed fluorescence under photoirradiation after exposure to vapors of small aromatic guests. The fluorescence intensity and maximum wavelength depended on the type of guest aromatic molecules, similar to the crystal. The naphthalenediimide derivative-absorbed papers showed vapochromic and mechanochromic properties.